Estimation of Incremental Import Potentials in the Soviet Union - Brock, John J.; Tarullo, P. Ronald (Journal of International Business Studies, 1977)
This paper analyzes the economic planning system of the USSR and presents a technique for estimating incremental import potentials for various commodities in the Soviet Union through the use of Soviet planning and production data. In order to demonstrate this technique, the paper focuses on machine tools and trucks.